PENGARUH KINERJA KEUANGAN SEBELUM DAN SESUDAH RIGHT ISSUE PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sinaga, Rafli Oktavia; Pasaribu, Dompak; Sagala, Farida (MTU PRESS, 2023)
This research aims to determine and analyze whether there are differences in financial performance before and after the Right Issue in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The financial ratios used are the Current Ratio, Debt to debt-to-equity ratio, Net Profit Margin, and Total Assets Turnover. The sample size for this study is 4. Secondary data is used, and the sampling method employed is purposive sampling. Parametric tests used are Paired Sample t-Test, and non-parametric tests used are Wilcoxon Signed Rank Test, with the assistance of SPSS 22 software. Based on the results of this research, it is indicated that there is no difference before and after conducting a Rights Issue in terms of Current Ratio and Debt to Equity, as determined by the Wilcoxon Signed Rank Test. Additionally, for the Net Profit Margin and Total Asset Turnover ratios, there is no difference before and after conducting a Rights Issue, as determined by the Paired Sample t-test.